The Role of Viscosity in Nanofluid as Heat Transfer Fluid: An Overview of Influential Factors - Nur Aaliyah Husna Mohd Zahid; Aleesya Humaira Mohd Helmi Firdaus; Maryam Mursyida Mohd Zamli Tajudin; Nor Athirah Izzah Zulkefli; Syukrina Imtiyaz Abdul Samat (Kolej PERMATA Insan, 2025)
Insan Junior Researcher International Conference & Innovation (iJURECON) 2025 : “STREAM for a Better Future/ editor : Ahmad Fuad Mohamad Amin, Nurul Shazwani Binti Mohamed, Rossidi Bin Usop, Abdel Rahman Ibrahim Suleiman Islieh Organised by Kolej PERMATA Insan 10-11 October 2025